THE ROLE OF ORGANIZATIONAL COMMITMENT AS A MEDIATION VARIABLE OF COMPENSATION AND MOTIVATION ON THE PERFORMANCE OF BUKIT DUABELAS NATIONAL PARK EMPLOYEES - Kurniawan, Herry; Ali, Hapzi; Hendrian Hendrian (Dinasti Publisher, 2022)
This study was conducted to analyze compensation and motivation on the performance of Bukit Duabelas National Park employees with organizational commitment as a mediating variable. The results showed that the description of compensation, motivation, organizational commitment and employee performance was running as it should. Compensation has no effect on organizational commitment and compensation has no effect on employee performance. Motivation has a positive and significant effect on organizational commitment, but motivation has no effect on employee performance. Organizational commitment has a positive and significant effect on employee performance, but organizational commitment is not proven to mediate compensation on performance employees with the nature of the competitive-mediating relationship and subsequently organizational commitment has been proven to mediate motivation on employee performance with the nature of the full-mediating relationship. The empirical findings above provide an illustration that the organizational commitment variable is able to mediate the motivational variable on employees performance, meaning that to improve the performance of the TNBD Hall employees, it is necessary to go through the organizational commitment variable.